1995
DOI: 10.1002/1097-4679(199509)51:5<626::aid-jclp2270510507>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

What's in a name? The MMPI-2 PTSD scales

Abstract: The MMPI‐2 post‐traumatic stress disorder scales (PK and PS) were examined with a sample of 96 outpatient anxiety disorder and 97 outpatient traffic accident subjects. PK and PS correlated 0.96 and showed highly similar correlations with MMPI‐2 validity, clinical, content and supplementary scales for both groups, which indicated that these scales are indices of MMPI first‐factor variance. This was supported by separate principal components analyses for each group, in which PK and PS contributed the most varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…A review by Wise (1996) found that the MMPI 8-2 profile best distinguished PTSD and other psychiatric patients. In contrast, Miller, Goldberg, and Streiner (1995) found little utility in using the MMPI-2 PTSD scales to identify patients with anxiety disorders from patients who were injured in traffic accidents (although few of the accident patients were diagnosed with PTSD).…”
mentioning
confidence: 98%
“…A review by Wise (1996) found that the MMPI 8-2 profile best distinguished PTSD and other psychiatric patients. In contrast, Miller, Goldberg, and Streiner (1995) found little utility in using the MMPI-2 PTSD scales to identify patients with anxiety disorders from patients who were injured in traffic accidents (although few of the accident patients were diagnosed with PTSD).…”
mentioning
confidence: 98%
“…With regard to the PK scale, findings are also somewhat ambiguous. Although many reports suggest adequate discrimination between groups using a cutoff score on the PK scale (Cannon, Bell, Andrews, & Finkelstein, 1987;Query, Megran, & McDonald, 1986; C. G. Watson et al, 1986), some studies suggest that the scale is best described as a measure of general distress not specific to PTSD (Gayton et al, 1986;Hyer, Boudewyns, O'Leary, & Harrison, 1987;Miller, Goldberg, & Streiner, 1995;Scheibe, Bagby, Miller, & Dorian, 2001).…”
mentioning
confidence: 99%
“…Higher scores on the Welsh’s Anxiety (A) scale indicated symptoms of anxiety, as well as general maladjustment, including psychological turmoil and poor functioning (Welsh, 1956). Also, Keane, Malloy, and Fairbank (1984), Graham, Ben-Porath, and McNulty (1999), and Miller, Goldberg, and Streiner (1995) demonstrated a relationship between the Post-Traumatic Stress Disorder (PK) scale and symptoms of general emotional distress and psychological maladjustment. Based on all the above research, we can assume that there is the potential for new recruits who score high in MMPI-2 to have mental health problems and possibly have difficulties with both interpersonal interactions and army training.…”
Section: Study 2: Predicting New Recruit Adjustment To Army Life Usinmentioning
confidence: 99%